2022
DOI: 10.1021/acsapm.1c01710
|View full text |Cite
|
Sign up to set email alerts
|

Superior Corrosion and UV-Resistant Highly Porous Poly(vinylidene fluoride-co-hexafluoropropylene)/alumina Superhydrophobic Coating

Abstract: The current research is devoted to fabricating a superhydrophobic coating on alumina surfaces via a facile one-step electrospinning technique. The wettability properties of the as-prepared coating were investigated. The polymeric coatings exhibited a water contact angle (WCA) of about 152° ± 3 and a sliding angle (SA) is 4 ± 2°. However, a WCA of 154 ± 2° and a SA of 3 ± 2° were recorded after the addition of Al2O3 nanoparticles. The wettability of the prepared coatings has also been inspected after exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…The chemical resistance test was conducted by immersing the PS/PDMS/PECA coating into different pH solutions (pH = 1, 3, 5, 7, 9, 12, 14) for 1 week followed by measurements of CA/SA values, solar reflectance, and emissivity. The UV resistance test was carried out using a QUV accelerated weathering machine (GB16776-2005, Zhongke Huanshi Instrument Co., Ltd., China). For one testing cycle, the sample was mounted and subjected to 8 h of UV exposure under an UV lamp (340 nm) with an intensity of 0.89 W/(m 2 nm) at 60 °C followed by 4 h moisture exposure by condensation at 50 °C.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The chemical resistance test was conducted by immersing the PS/PDMS/PECA coating into different pH solutions (pH = 1, 3, 5, 7, 9, 12, 14) for 1 week followed by measurements of CA/SA values, solar reflectance, and emissivity. The UV resistance test was carried out using a QUV accelerated weathering machine (GB16776-2005, Zhongke Huanshi Instrument Co., Ltd., China). For one testing cycle, the sample was mounted and subjected to 8 h of UV exposure under an UV lamp (340 nm) with an intensity of 0.89 W/(m 2 nm) at 60 °C followed by 4 h moisture exposure by condensation at 50 °C.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…15 The authors also produced a polyurethane superhydrophobic coating using 8 wt% nanosilica sprayed over porcelain insulators. 16 The coating demonstrated high mechanical strength and UV resistance. Some researchers developed a superhydrophobic coating utilizing a suspension of SiO 2 -powder and SiO 2 -sol using a sol−gel process including tetraethoxysilane, perfluorodecyltriethoxysilane, ethanol, nitric acid, and hydrochloric acid.…”
Section: Introductionmentioning
confidence: 98%
“…Field studies have shown that RTV coatings have a maximum lifetime of 10 years under severe contamination conditions . The authors also produced a polyurethane superhydrophobic coating using 8 wt% nanosilica sprayed over porcelain insulators . The coating demonstrated high mechanical strength and UV resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Superhydrophobic surfaces require an appropriate level of surface roughness and low surface energy. Most coatings incorporate nanoparticles or fibers as fillers to construct a hierarchically structured rough surface, such as Al 2 O 3 , SiO 2 , CNFs, graphene, and carbon nanotubes (CNTs). …”
Section: Introductionmentioning
confidence: 99%